THE EFFECT OF STEAMING TIME OF THE DOUGH ON THE PREFERENCE LEVEL OF SQUID CRACKERS (Loligo sp.) - Pratama, Rusky Intan; Andriani, Yuli; Rostini, Iis; Filardi, Tara (Jurnal Perikanan Unram, 2025)
Squid (Loligo sp.) is a high-value fishery commodity with rich nutritional content, so it has the potential to be developed into various nutritious processed products such as squid crackers. Squid cracker processing involves several important stages, where the steaming process plays a major role in determining the physical and organoleptic quality of the final product. This study aimed to analyze the effect of steaming time of the dough on the preference level of squid crackers (Loligo sp.) to produce a product favored by panelists, as well as to examine the physical properties of the preferred squid crackers. The research was conducted at the Fishery Product Processing Laboratory, Faculty of Fisheries and Marine Sciences, and the Testing Laboratory, Faculty of Agro-Industrial Technology, Padjadjaran University, from December 2024 to February 2025. An experimental method was used with three different steaming durations: 30 minutes, 45 minutes, and 60 minutes. The parameters observed were organoleptic characteristics assessed by 20 semi-trained panelists including appearance, aroma, taste and texture, as well as physical properties such as hardness and expansion power. Data obtained from the results of the Hedonic test observations were analyzed using the Friedman test and data obtained from the hardness test were analyzed descriptively and the expansion power test was analyzed using ANOVA analysis. The research results showed that squid crackers with a steaming time of 45 minutes were the most preferred treatment by the panelists with an average value of appearance of 7.9; aroma 7.4; taste 8.0; and texture 8.0. The results of the hardness test of treatment B were 2,301.632 gf and the swelling power test was 56.57%.